A Case of Succinyl-CoA:3-Oxoacid CoA Transferase Deficiency Presenting with Severe Acidosis in a 14-Month-Old Female: Evidence for Pathogenicity of a Point Mutation in the OXCT1 Gene - Zheng, Daniel J.; Hooper, Michael; Spencer-Manzon, Michele; Pierce, Richard W. (Journal of Pediatric Intensive Care, 2018)
We describe a case of succinyl-CoA:3-oxoacid CoA transferase (SCOT) deficiency in an otherwise healthy 14 month-old female. She presented with lethargy, tachypnea, and hyperpnea with hypoglycemia and a severe anion gap metabolic acidosis. Early management included correction of the acidosis and metabolic support with dextrose and insulin. Inborn errors of metabolism are rare outside the neonatal period. However, SCOT deficiency may present at older ages. Maintaining a high index of suspicion, immediate transfer to a pediatric intensive care unit, and prompt metabolic support are key to achieving a favorable outcome.
Keywords: succinyl-coA:3-oxoacid CoA transferase deficiency; OXCT1 gene; ketoacidosis